IMPROVING THE EFFECTIVENESS OF COMPETITIVE ACTIVITY OF FOOTBALL PLAYERS AGED 14-15 YEARS ON THE BASIS OF THE DEVELOPMENT OF POWER ABILITIES PROPER - Bedarkov K.I.; Shilko V.G. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to prove the effectiveness of the methodology, which includes a set of special physical exercises aimed at developing the strength abilities of young athletes. Methods and structure of the study. The algorithm of the experiment assumed a consistent solution of the following tasks: the development of a complex of physical exercises and its implementation through the method of circular training (experimental group) and the repeated method (control group), which involve the purposeful development of the actual strength abilities and the assessment of the influence of the developed and traditional methods on the indicators of competitive activity in in general. The training process using both methods was carried out for six weeks, two workouts per week. Results and conclusions. For the development of self-strength abilities, special exercises of varying complexity were selected: YWTL, crunches with twisting, pike push-ups, twisting with a twist of the pelvis, "superman", pull-ups in a horizontal position, "bike", flexion and extension of the forearms (raising the biceps) with bent legs, push-ups from the back with a support on three points, lifting straight legs from a prone position, etc. The results of the pedagogical experiment confirmed significant changes in the achievements of the representatives of the experimental group, who practiced according to the developed methodology, in comparison with the athletes of the control group, whose classes were organized according to the traditional methodology, applied without taking into account the peculiarities of the sport. The authors state that one of the effective means of educating self-strength abilities of young football players is a special set of physical exercises (16 exercises), applied on the basis of the circuit training method, which has proven its advantage over a set of traditional exercises using a repeated method and which will contribute to increasing the effectiveness of preparing young football players for competitive activities in general.